Perceived Disempowerment as a Deterrent of Inpatient Complaining - Khadir, Fezeena; Swamynathan, R. (Indian Journal of Marketing, 2017)
Purpose : This paper attempted to understand the felt disempowerment that discourage consumers to voice their complaints in spite of their dissatisfaction with hospital services. Design/Methodology/Approach : Data collected from 312 dissatisfied inpatients who were admitted and discharged from various 100+ bedded private and cooperative hospitals across Kerala revealed that a majority dissuaded from overt complaining behaviours despite dissatisfaction. Instead, they resorted to covert complaining behaviours like engaging in negative word of mouth with friends, relatives, or other inpatients ; switching behaviour ; exit ; or just keeping silent. Findings : Factor analysis revealed that ’powerlessness’ and ’subservient’ attitude perceived by inpatients in hospitals deterred them from overt complaining behaviours like voicing, seeking third party redressal, or legal action. Bivariate analysis found out that while a significant difference could be established between dissatisfied inpatients holding different levels of occupation, admitted to hospitals belonging to various zones and with different levels of medical awareness, no true difference was observed between respondents possessing different socioeconomic and demographic status, nature of action resorted, admitted in different types of hospitals, and various durations of hospital stay with respect to their levels of perceived disempowerment. Research Limitations/ Implications : The fact that patients are disempowered gives an upper hand to the provider, principally in a credence service like health care. As the respondents who participated in the survey opted to either switch provider or engage in negative word-of-mouth with friends and relatives than overtly complaining, their actions can be viewed as unfavorable from the health care providers’ perspective. Practical Implications : Only if the hospitals know that they have caused some sort of discomfort or dissatisfaction to their customers will they get an opportunity to rectify their mistakes. Originality/Value : This study brought to light very important information that hospitals in Kerala need to be cautious about.